2002
DOI: 10.1248/jhs.48.473
|View full text |Cite
|
Sign up to set email alerts
|

Science of Bamboo Charcoal: Study on Carbonizing Temperature of Bamboo Charcoal and Removal Capability of Harmful Gases.

Abstract: We examined the relationship between the carbonizing temperature of bamboo carbide made from Moso bamboo (Phyllostachys pubescens) and the removal effect of harmful gases and odorants, and the use of a bamboo charcoal as a countermeasure for "Sick Building Syndrome" or "Chemical Sensitivity" and the use as a deodorant. With regard to the carbonizing temperature of the bamboo charcoal, a temperature sensor was installed inside each bamboo material and the carbonizing temperature was controlled at 500, 700 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(114 citation statements)
references
References 8 publications
5
106
2
1
Order By: Relevance
“…Asada et al reported that micropores of 0.5-2 nm sizes were effective for the physical adsorption of several hazardous gases like formaldehyde, toluene, benzene, ammonia, and indole. (Asada et al 2002). Mesopores of 6.5 and 15 nm sizes were reported together with macropores of 60 and 450 nm sizes, and the pore size distribution depended on the temperatures for the bamboo charcoal preparation (500, 700, and 1000°C).…”
Section: Introductionmentioning
confidence: 92%
“…Asada et al reported that micropores of 0.5-2 nm sizes were effective for the physical adsorption of several hazardous gases like formaldehyde, toluene, benzene, ammonia, and indole. (Asada et al 2002). Mesopores of 6.5 and 15 nm sizes were reported together with macropores of 60 and 450 nm sizes, and the pore size distribution depended on the temperatures for the bamboo charcoal preparation (500, 700, and 1000°C).…”
Section: Introductionmentioning
confidence: 92%
“…Through an application of this approach, they observed their removal at 92 and 95 %, respectively. In continuation of this effort, Asada et al (2002) utilized Bamboo charcoal for the removal of formaldehyde, acetaldehyde, and benzene from waste Fig. 4 Comparison of odorant concentration levels across transfer and process line: On X-axis, ?…”
Section: Effectiveness Of Odor Control Between Different Treatment Unitsmentioning
confidence: 99%
“…9 In short, Moso bamboo (Phyllostachys pubescens) was carbonized at 500˚C for 1 h, and the obtained porous carbon was then crushed and sieved with a particle diameter of 125 -1000 µm. Before the porous carbon was packed in a glass tube, it was dried at 115˚C for 3 h.…”
Section: Preparation Of Sampling Tubementioning
confidence: 99%
“…In a previous report, 9 we described that porous carbon carbonized at 500˚C (hereafter referred to as 500˚C porous carbon) was superior to other adsorbents regarding the ammonia adsorption effect. Porous carbon at 500˚C has many acidic groups, such as carboxyl groups and phenolic hydroxyl groups, on the surface, because the thermolysis of cellulose or lignin, which are the main components of wood material, actively occurs at 400 -500˚C, and many acidic groups are formed by thermolysis.…”
mentioning
confidence: 99%